Black holes, tides, and curved spacetime : understandig gravity - Schumancher, Benjamin (The Great Courses. Science & Mathematics. Physiscs, 2013)
24 Conferencias del Profesor de Física Benjamin Schumancher sobre la Fuerza de Gravedad